Television Shopping at Home to Alleviate Loneliness Among Older Consumers - Min-Sun Lee; Jihye Park (Asia Marketing Journal, 2017)
Despite widespread awareness of the importance of a middle-aging and older consumer market, it is surprising that very little research has been conducted on their in-home shopping behavior. Therefore, this study focused on middle-aging and older female television home shoppers and examined the effects of persuasive mentions of the show host and parasocial interaction on social involvement, perceived loneliness, mood, perceived risk and unplanned buying tendency. A total of 109 middle-aged and older female television shoppers responded. Results of path analysis revealed that persuasive mentions did not influence parasocial interaction. However, as middle-aging and older consumers more para-socially interacted with the host, they were likely to use television shopping for alleviating loneliness. Practical and theoretical implications were discussed.